Unstable lesions of the forearm: Terminology, evaluative score and synoptic table. (March 2023) - Fontana, Maurizio; Rotini, Marco; Battiston, Bruno; Artiaco, Stefano; Dutto, Elisa; Sard, Arman; Colozza, Alessandra; Vicenti, Giovanni; Cavallo, Marco; Rotini, Roberto
Highlights: The forearm is a separate functional unit stabilised by three constraints. Injury to two causes transversal instability. Lesion damage to three constraints causes longitudinal and transverse instability. An alphanumeric classification is presented to describe the four patterns and variants of ULF. Clinical results are evaluated by the 100-point Forearm Italian performance score. A table is proposed to guide timely diagnosis and identification of injured structures in acute and chronic lesions. Abstract: The term "unstable lesions of the forearm" (ULF) was born to more easily describe how a partial or complete instability of the forearm unit might occur due to a traumatic loss of the transverse or longitudinal connection between the radius and ulna. For such an alteration to occur, at least two of the three main osteoligamentous locks (proximal, middle and distal) must be interrupted, often in association with a radial and/or ulnar fracture. Examining the historical patterns (Monteggia, Galeazzi, Essex–Lopresti and criss-cross lesions) and variants described in the literature, out of a total of 586 recorded interventions for forearm trauma, two elbow teams and one wrist team selected 75 cases of ULF. The aim was to describe the instability depending on its clinical and radiographic features, together with the anatomopathological evolution of the lesions based on the time of diagnosis and treatment. The clinical results, evaluated using a new score (FIPS) the Forearm Italian Performance, revealed a correlation between earlier diagnosis and treatment and a better score. The authors suggest a synoptic table that describes 1) the type of instability (proximal transverse, distal transverse, longitudinal and transverse, proximal and distal transverse), 2) classic patterns and variants with characteristic lesions and evolution over time (acute, chronic dynamic, chronic static) and 3) the three forearm constraints and segmental involvement of radius and/or ulna using an alphanumeric classification. Finally, some generic surgical suggestions are proposed.